Implementation of a resident-led patient safety curriculum - Hanes, Lauren; Afifi, Jehier; Lynk, Andrew; Manos, Sarah (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Implication StatementThe Royal College of Physicians and Surgeons of Canada has made Quality Improvement and Patient Safety (QIPS) a priority in residency education, however, implementation is limited by the heterogeneity of previously published curricula. We created a longitudinal resident-led patient safety (PS) curriculum using relatable, real-life PS incidents (PSIs) and an analysis framework. Implementation was feasible, well received by residents and demonstrated significant improvement in residents’ PS knowledge, skills, and attitudes. Our curriculum built a culture of PS within a pediatric residency program, promoted engagement in QIPS practices early in training, and filled a gap in the current curriculum teaching.